Kontribusi Majelis Taklim Irsyadus Sholihin Dalam Meningkatkan Ibadah Masyarakat Desa Bandar Khalipah Kecamatan Percut Sei Tuan - Rahma, Afifatuh; M, Mahariah; Pulungan, Juli Julaiha (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research is titled The Contribution of the Taklim Irsyadus Sholihin Council in Increasing the Worship of the People of Bandar Khalipah Village, Percut Sei Tuan District. This research aims to know the response and interest of the community in participating in the activities of the Irsyadus Sholihin taklim assembly, the contribution of the assembly for the community, the contribution of the Irsyadus Sholihin taklim assembly in increasing community worship, forms of worship education activities in the Irsyadus Sholihin taklim assembly.  This research uses qualitative research methods with a phenomenological approach. The data collection technique uses observation, interview, and database study. The data analysis technique by reducing data, presenting data, and drawing conclusions.  The results of this study revealed that 1) the response and interest of the community in participating in all activities in the taklim assembly were very good, and the taklim assembly became one of the learning platforms that discussed the knowledge of the Islamic religion. With this activity, the community is very enthusiastic in following it and the interest in learning religious knowledge is very high. 2) This taklim assembly significantly contributes to increasing prayer by how to pray and devotion, almsgiving the importance of sharing with others, and friendship through the strengthening of social relations between members of the community. 3) As for the forms of activities that are carried out in this tak'lim assembly are the same as in general, the ta'lim assembly not only functions as a means of teaching religion, but also as a forum to strengthen Islamic preaching and increase social awareness.